Covid-19 pandemic related disclosures in corporate reports of Portuguese listed companies: an interpretation of evidence provided by accounting information systems - Carmo, Cecília M.R. (2023)
This work analyzes how Portuguese listed companies disclosed pandemic-related information in their annual reports in the years 2019 and 2020, focusing on the sections where information was presented, the Corporate Social Responsibility (CSR) actions implemented, and the risks disclosed. Based on a manual content analysis, this work provides preliminary evidence on corporate disclosures made in the pandemic context, suggesting that institutional forces and stakeholder groups may have influenced the information disclosed and provided by accounting information systems.